International Financial Integration of East Asia and Pacific - Didier, Tatiana (World Bank, Washington, DC, 2016)
This paper documents how economies in the East Asia and Pacific (EAP) region have integrated financially with the rest of the world since the 1990s. First, the region is increasingly more connected with itself and with other economies. Although economies in the North capture the bulk of the region's investments, EAP's connectivity with the South has grown relatively faster. Second, the largest economies in the region (China, Japan, the Republic of Korea, and Singapore) account for most of EAP's cross-border investments. Third, compared with the other South regions, EAP displays a higher level of intraregional and outward investments, reflecting the region's role as a net capital exporter. The differences with South regions are persistent over time. Although EAP lags behind as a destination of foreign investments, inflows to developing EAP economies are comparable to those to other South regions. Fourth, EAP's financial integration is related to its international trade patterns.